Put Out Waste Bones-they make glue for aircraft-poster (United Kingdom)
1942 1939-1945 "Put Out Waste Bones-they make glue for aircraft-poster" [HFR0004], c. 1940 Ministry of Supply poster issued as part of the salvage drive.